On processes controlling fine particulate matters in four Indian megacities. (November 2019) - Anand, Vrinda; Korhale, Nikhil; Rathod, Aditi; Beig, Gufran
Abstract: The data of most toxic particulate pollutants (PM2.5 and PM10 ) obtained from a dense SAFAR observational network in four Indian mega cities (Delhi, Mumbai, Pune and Ahmedabad) located in North-West part of India, not very far from each other, have been presented in this work. In spite of similar kind of sources of anthropogenic local emissions, each city has its unique air pollution footprints. The paper addresses the role of geographical location based prevailing meteorology in determining the variability of particulate matter in different seasons and processes responsible for the same. We hereby demonstrate that although Delhi has the highest level of particulate matters, the percentage share of PM2.5 in PM10 is highest for Mumbai (60%) as compared to 50% of Delhi. The pollutant levels of Delhi, Mumbai and Pune show strong seasonal variability whereas Ahmedabad does not show any significant variation for summer to winter. We have further discussed that the landlocked geography of Delhi and coastal location of Mumbai often play a dominant role in the distribution of air pollutants. Hence, the mitigation options require specific consideration of integrated approach for each city. Graphical abstract: Image 10186 Highlights: The magnitude of particulate matter concentrations is highest at Delhi as compared to Mumbai, Ahmedabad and Pune due to its peculiar weather and being a landlocked region. Although the particulate matter concentrations are highest in Delhi the ratio of PM2.5 /PM10 is lowest here and it is found to be highest in Mumbai. The emissions in all the four cities are comparable yet we see significant differences in the particulate matter concentrations due to the prevailing meteorology and geography. Abstract : Four Indian cities having high anthropogenic emissions show significant variability in particulate matter concentrations due to its geographical location and local meteorology.